2022
DOI: 10.1097/01.asw.0000801532.60229.78
|View full text |Cite
|
Sign up to set email alerts
|

Does pH Influence the Bacterial Profile of Chronic Lesions? An Analysis of Venous Ulcer Samples

Abstract: OBJECTIVE To analyze the pH of venous ulcers and their relationship with the quantitative and qualitative bacterial profile of the wounds. METHODS Cross-sectional study carried out through data collection and microbiologic analyses of samples obtained from 35 venous ulcers. Investigators performed pH measurement with indicator strips and collected biologic material using swabs. After aerobic and anaerobic cultivation, colony-forming units (CFUs) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
(71 reference statements)
0
5
0
1
Order By: Relevance
“…Chronic VLU is characterized by an alkaline pH ranging from 7.9 to 8.7, along with bacteria such as S. aureus and P. aeruginosa. Interestingly, no direct association has been found between the bacterial profile and pH levels in these ulcers, although infection indeed raises the wound pH [30]. Additionally, for every 1-unit change in pH, a corresponding change in wound size of approximately 116.05 mm 2 can be expected [32].…”
Section: Wound Bed Phmentioning
confidence: 93%
See 3 more Smart Citations
“…Chronic VLU is characterized by an alkaline pH ranging from 7.9 to 8.7, along with bacteria such as S. aureus and P. aeruginosa. Interestingly, no direct association has been found between the bacterial profile and pH levels in these ulcers, although infection indeed raises the wound pH [30]. Additionally, for every 1-unit change in pH, a corresponding change in wound size of approximately 116.05 mm 2 can be expected [32].…”
Section: Wound Bed Phmentioning
confidence: 93%
“…According to the studies conducted by Serra et al [36], Rabello Sergio et al (2022) [30], and Thomsen et al (2010) [66], the most common bacteria found in infected venous ulcers include Staphylococcus aureus, Pseudomonas aeruginosa, and Corynebacterium striatum. S. aureus and P. aeruginosa were identified as the most frequently observed bacterial species in venous ulcers, according to both Serra et al (2014) and Rabello Sergio et al (2022) [30] studies. Thomsen et al (2010) [66] also reported that S. aureus, P. aeruginosa, and Enterococcus faecalis were frequently observed in chronic VLU when culture-based methods were used.…”
Section: Infection and Its Impact On The Wound Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…São necessárias várias etapas de um processo de avaliação para identificar problemas que possam contribuir para o agravo desse tipo de lesão. A avaliação da Brazilian Journal of Development, Curitiba, v.9, n.5, p. 18298-18312, may., 2023 deficiência circulatória, profundidade, extensão, estado nutricional, raça, idade e tempo de início da ferida (9).…”
Section: Fatores Importantes Que Favorecem a Cicatrizaçãounclassified